2015
DOI: 10.1097/md.0000000000000573
|View full text |Cite|
|
Sign up to set email alerts
|

Visceral Adipose Tissue Area as an Independent Risk Factor for Elevated Liver Enzyme in Nonalcoholic Fatty Liver Disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…The methods employed in this study have been described in detail elsewhere . Hepatic ultrasonography was performed by experienced radiologists who were blinded to the clinical and laboratory data at the time of the procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods employed in this study have been described in detail elsewhere . Hepatic ultrasonography was performed by experienced radiologists who were blinded to the clinical and laboratory data at the time of the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The methods employed in this study have been described in detail elsewhere. 12,19,22 Hepatic ultrasonography was performed by experienced radiologists who were blinded to the clinical and laboratory data at the time of the procedure. Fatty liver was diagnosed by ultrasonographic findings (Acuson, Sequoia 512, Siemens, Mountain View, CA, United States) based on liver brightness, echo contrast between the hepatic and renal parenchyma, vascular blurring and deep attenuation.…”
Section: Hepatic Ultrasonographic Examinationsmentioning
confidence: 99%
“…In fact, a correlation between the visceral abdominal fat detected by CT scan and the degree of hepatic steatosis has previously been demonstrated. 19,23 Therefore patients with steatosis might feature an increase in mesenteric visceral fat that displaces the bowel, particularly the colon, thereby hampering the visualization of the liver and the pancreas and mimicking the presence of excessive intestinal gas. However, these…”
Section: Discussionmentioning
confidence: 99%
“…Visceral adipose tissue (VAT) area is more directly related to NAFLD than is the body mass index (BMI) as a surrogate marker of general obesity . We previously reported that increased VAT area is independently associated with NASH or significant fibrosis .…”
Section: Introductionmentioning
confidence: 99%
“…Visceral adipose tissue (VAT) area is more directly related to NAFLD than is the body mass index (BMI) as a surrogate marker of general obesity. 7,8 We previously reported that increased VAT area is independently associated with NASH or significant fibrosis. 9 Several studies have reported that an increased visceral fat is associated with metabolic syndrome in metabolically obese, normal-weight (MONW) subjects.…”
Section: Introductionmentioning
confidence: 99%